Biochemical and functional quality assessment of platelet concentrates - Vacić, Nebojša; Antić, Ana; Stanojković, Zoran; Vučić, Miodrag; Lazarević, Milan (Vojnosanitetski pregled, 2021)
Background/Aim. Preparation of platelet concentrate (PC) from a unit of whole blood is a method dependent on a number of factors, which alone or together, can have a significant impact on the quality of the final product. Quality of PCs is determined with criteria defined in the Guide to the preparation, use and quality assurance of the Council of European Committee for Blood Transfusion. The aim of the study was to analyze the quality of PCs prepared from buffy coat (BC) and to allocate the factors of improvement and standardization of the quality of PCs. Methods. The study included a total of 80 PCs prepared from BC according to the standard procedure in the Blood Transfusion Institute Niš. The quality of PCs was determined according to the product volume and laboratory testing on the first (PC1), the third (PC3) and the fifth day (PC5) of the PC storage. The following parameters were determined: platelets, residual erythrocytes and leukocytes count, gas analysis [partial pressure of oxygen, carbon dioxide (pO2, pCO2)], pH, sterility and platelet aggregation triggered by using 3.2, 6.4 and 9.6 μg collagen/mL (impedance aggregometry). Results. There were significantly lower platelet count, pO2, pCO2 and pH in the PC3 and PC5 samples (p < 0.001). Except for the fulfillment of the criteria for platelet count, all the other quality parameters were in accordance with recommended criteria. Platelet aggregation for all the concentrations of collagen showed a decrease during the storage period, with statistically significant differences for PC3 and PC5 as compared to PC1 (p < 0.01). There was statistically significant decrease in activity of PCs triggered with higher concentrations of collagen (6.4 and 9.6 μg collagen/mL) in comparison with lower concentration of collagen (3.2 μg collagen/mL). Conclusion. Platelet count, evaluated biochemical parameters and the platelet function were significantly changed during the storage period. In order to improve the quality of PCs it is important to store the products under proper conditions, change the type of plastic bag for PC storage and use platelet additive solutions (PAS) instead of plasma.